واقع اختيار الطالب للتخصص الجامعي بين الدوافع الشخصية والأسرية - يسعد, فوزية; جردير, فيروز (جامعة الوادي - University of Eloued, 2022)
ما أن يسعد الطالب بنتائجه في الثانوية ويكاد يفرغ منها، إلا وتواجهه معركة صعبة تبدو واضحة عندما يبحث عن التخصص الجامعي المناسب، فيشعر وكأنه تائه بين إشباع ميوله الشخصية نحو اختيار التخصص المناسب، وبين رغبة الوالدين في إلحاقه لدراسة بعينها قد تخالف رغباته وميوله المستقبلية.. أيضا يتوقف الأمر على مدى ما يوفره المجتمع من تخصصات قد تلبي ميوله الذاتية أو لا تلبيها وفقا لاحتياجات سوق العمل.. فيقع بين رغبة الفرد، ورغبة الأسرة، ورغبة سوق العمل. حيث تعتبر مرحلة اختيار الطالب للتخصص من أهم القرارات التي يتخذها في مشواره الأكاديمي وقرار اختيار التخصص هو قرار حياتي بالدرجة الأولى ويجب أن يحوز على الاهتمام والسؤال والبحث وقد جاءت هذه الدراسة للكشف عن واقع اختيار الطالب الجامعي بين الدوافع الشخصية والأسرية وقد حاولنا في هذه المداخلة الإجابة على التساؤلات التالية ؟ - ما هي أهم العوامل التي تتدخل في اختيار الطالب للتخصص الجامعي؟ - هل اختيار الطالب للتخصص الجامعي يعود لدوافع شخصية أم أسرية أو لمتغيرات أخري؟. Summary: As soon as the student is pleased with his results in secondary school almost emptied, but faced with a difficult battle seems obvious when looking for the appropriate university specialization, feels as if lost between satisfying his personal tendencies to choose the appropriate specialization, and the desire of parents to attach a study that may violate his wishes and future tendencies ... It also depends on the extent to which the community provides specialties that may meet its narrow or unmet expectations in accordance with the needs of the labor market ... between the desire of the individual, the desire of the family, and the desire of the labor market. Where the stage of the student's choice of specialization is one of the most important decisions he takes in his academic career and the decision to choose the specialization is the decision of my life in the first place and must have the interest and the question and research This study came to reveal the reality of the student's choice between personal and family motives. On the following questions? What are the most important factors that interfere with the student's choice of university specialization? Is the student's choice of university specialization due to personal or family motives or other variables?
مقال
Keywords: الطالب الجامعي, الاختيار,الدوافع; universityStudent, Testing, Motives